Encuentros - Spinelli, Emily; Rosso-O'Laughlin, Marta (New York : Holt, Rinehart and Winston, Inc., 1988)
This textbook emphasizes a proficiency approach to teaching listening comprehension, speaking, reading, writing, and culture.
Contents: Spanish and English. -- Maps on lining papers. -- Binding error slip inserted.
Includes index.
Keywords: SPANISH LANGUAGE -- TEXTBOOKS FOR FOREIGN SPEAKERS -- ENGLISH